Phylogenetic relationships among sections Vicia, Sepium and Lathyroides of Vicia subgenus Vicia: isozyme evidence. (October 2015) - Jaaska, Vello
Abstract: Variation of 16 isozymes in Vicia barbazitae and in two couples of morphologically similar vetch species, Vicia grandiflora – Vicia qatmensis and Vicia lathyroides – Vicia cuspidata, in comparison with seven other species of sections Vicia and Sepium is described in order to get new evidence about their differentiation, phylogenetic and sectional position. The cladistic parsimony analysis of the isozyme data using Vicia bithynica of section Pseudolathyrus as an outgroup placed V . barbazitae, V . qatmensis, V . grandiflora and Vicia incisa in the same major clade together with Vicia sepium, the type species of section Sepium (syn. Atossa ). The isozyme data thus support revised circumscription of sections Vicia and Sepium by transferring V . barbazitae, V . grandiflora, V . qatmensis and V . incisa, currently placed in section Vicia, to section Sepium . Vicia grandiflora and V . qatmensis differ in orthozymes of PGD-A, but are placed in the same subclade of sister species as both differ from the other species in shared orthozymes of FDH-A, PGM-A, DIA-B and AAT-C. Vicia cuspidata and V . lathyroides differ by unique orthozymes of MDH-B, PGM-A, SKD-A and SOD-B, but are placed in the same subclade of sister species as both differ from the other species in shared orthozymes of FDH-A, IDH-A, MDH-A and PGI-B. Highlights: The cladistic parsimony analysis of isozyme characters placed Vicia barbazitae, Vicia qatmensis, Vicia grandiflora and Vicia incisa in the same major clade together with V . sepium, the type species of section Sepium (syn. Atossa ). Morphologically similar V . grandiflora and V . qatmensis are divergent by orthozymes of PGD-A, but are placed in the same subclade of sister species as both differ from the other species by shared orthozymes of FDH-A, PGM-A, DIA-B and AAT-C. Morphologically similar V . cuspidata and V . lathyroides are divergent by orthozymes of PGI-B, PGM-A, SKD-A and SOD-B, but are placed in the same subclade of sister species as both differ from the other species in shared orthozymes of FDH-A, IDH-A, MDH-A and PGI-B.